The Roles of Motilin and Ghrelin in Gastrointestinal Motility. (27th December 2009) - Ohno, Tetsuro; Mochiki, Erito; Kuwano, Hiroyuki
Abstract : In structure, ghrelin resembles motilin. The two peptides are considered to be members of the motilin-ghrelin peptide family. Motilin is considered to be an endocrine regulator of the interdigestive migrating contractions, the fasted motor pattern in the gastrointestinal (GI) tract. It has been reported that ghrelin stimulates GI motility. The gastrokinetic capacity of ghrelin has been well documented in the rodent. However, there have been few positive reports of the gastrokinetic capacity of ghrelin in dogs. Some reports with human subjects have shown that an i.v. ghrelin injection accelerated gastric emptying of a meal and improved meal-related symptoms. These results suggest that ghrelin has potential as a prokinetic. However, it seems unlikely that plasma ghrelin would play a physiological role in these digestive physiological events and stimulate gastric emptying, as these outcomes would appear to be in contradiction with the suppression of the endogenous release of ghrelin after eating. The physiological roles of ghrelin need to be clarified.